2013
DOI: 10.4149/neo_2013_046
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, anti-carcinogenic and antioxidant properties of the most frequent plant volatiles

Abstract: Flowers, berries, leaves, barks and roots of different plants have been used through the ages as a source of flavor in food and perfume preparations. The volatiles responsible for the flavor of botanicals can be extracted from the plant material as "essential oils" (EOs), called also volatile oils or ethereal oils. The term essential is intended to indicate that the oil is the fragrant essence of the plant from which it is extracted. EOs are constituted by hydrocarbons (monoterpenes and sesquiterpenes) and oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 81 publications
2
18
0
Order By: Relevance
“…The antioxidative activity of eugenol, measured as DPPH radical-scavenging activity, and thymol, measured as Trolox equivalent antioxidant capacity, was observed at as low concentration as 1 ppm (Slameňová et al, 2009) and 2.2 ppm (Ündeger et al, 2009), respectively. Further work confirmed the antioxidative effects of thymol and eugenol in assays demonstrating their reducing power and radical scavenging capacity, but only thymol was genoprotective against H 2 O 2induced oxidative DNA damage in colonocyte and hepatocyte cell lines (Horváthová et al, 2014;Slameňová & Horváthová, 2013). This is confirmed by our study where pre-exposure to thymol was genoprotective from 12.5 to 125 ppm.…”
Section: Toxicology and Chemical Food Safetysupporting
confidence: 84%
“…The antioxidative activity of eugenol, measured as DPPH radical-scavenging activity, and thymol, measured as Trolox equivalent antioxidant capacity, was observed at as low concentration as 1 ppm (Slameňová et al, 2009) and 2.2 ppm (Ündeger et al, 2009), respectively. Further work confirmed the antioxidative effects of thymol and eugenol in assays demonstrating their reducing power and radical scavenging capacity, but only thymol was genoprotective against H 2 O 2induced oxidative DNA damage in colonocyte and hepatocyte cell lines (Horváthová et al, 2014;Slameňová & Horváthová, 2013). This is confirmed by our study where pre-exposure to thymol was genoprotective from 12.5 to 125 ppm.…”
Section: Toxicology and Chemical Food Safetysupporting
confidence: 84%
“…These low molecular weight compounds are not practically soluble in water [35]. Monoterpenes, sesquiterpenes, oxygenated monoterpenes, oxygenated sesquiterpenes, phenolics and others [17,36] are the major constituents that provide the characteristic aroma and biological properties to EOs. To avoid the toxic effects of residual organic solvents, relatively less toxic SDEOs such as AG and ER SDEO (Tables 3-5) are a new and potential therapy to regulate Th1/Th2 immune balance and inhibit an inflammatory response without compromising an immune defense.…”
Section: The Correlation Between Pro-/anti-inflammatory Cytokine Secrmentioning
confidence: 99%
“…Most EOs exude a special aroma that may be useful for aromatherapy. Increasingly more in vitro and in vivo studies have demonstrated EO bioactivities, including antioxidant, antimicrobial, anti-inflammatory and anti-cancer effects [15][16][17]. EOs plays multiple roles in immune-regulation, including immune activation, inhibition or regulation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Light Thai massage in 94 patient's, ages 30-70 with colorectal cancer, after 7-10 day course of chemotherapy that were enrolled in a one week RCT study with 0.5 ml of ginger essential oil in coconut oil had improved cellular immunity as measured by CD4/CD8 ratios and improved self-rated symptom severity scores [50]. These components of essential oils commonly occur in food as eucalyptol, eugenol, borneol, carvacrol and thymol have differing anti-oxidative, anti-mutagenic and anti-carcinogenic properties in the laboratory [51]. There is a role for natural phenolic compounds from essential oils, in particular eugenol, in cancer chemoprevention via the regulation of the cell cycle [52].…”
Section: Metabolomics To Measure Effects Of Supplementsmentioning
confidence: 99%